Orf virus interleukin‐10 and vascular endothelial growth factor‐E modulate gene expression in cultured equine dermal fibroblasts. Issue 5 (22nd August 2016) - Wakelin, Kirsty A.; Wise, Lyn M.; Bodaan, Christa J.; Mercer, Andrew A.; Riley, Christopher B.; Theoret, Christine L.
Abstract : Background: Wounds in horses often exhibit sustained inflammation and inefficient vascularization, leading to excessive fibrosis and clinical complications such as "proud flesh". Orf virus‐derived proteins, vascular endothelial growth factor (VEGF)‐E and interleukin (ovIL)‐10, enhance angiogenesis and control inflammation and fibrosis in skin wounds of laboratory animals. Hypothesis/Objectives: The study aimed to determine if equine dermal cells respond to VEGF‐E and ovIL‐10. Equine dermal cells are expected to express VEGF and IL‐10 receptors, so viral protein treatment is likely to alter cellular gene expression and behaviour in a manner conducive to healing. Animals: Skin samples were harvested from the lateral thoracic wall of two healthy thoroughbred horses. Methods: Equine dermal cells were isolated using a skin explant method and their phenotype assessed by immunofluorescence. Cells were treated with recombinant proteins, with or without inflammatory stimuli. Gene expression was examined using standard and quantitative reverse transcriptase PCR. Cell behaviour was evaluated in a scratch assay. Results: Cultured cells were half vimentin +ve fibroblasts and half alpha smooth muscle actin +ve and vimentin +ve myofibroblasts. VEGF‐E increased basal expression of IL‐10 mRNA, whereas VEGF‐A and collagenase‐1 mRNA expression was increased by ovIL‐10. In cells exposed to inflammatory stimulus, both treatments dampened tumour necrosis factor mRNA expression, and ovIL‐10 exacerbated expression of monocyte chemoattractant protein. Neither viral protein influenced cell migration greatly. Conclusions and clinical importance: This study shows that VEGF‐E and ovIL‐10 are active on equine dermal cells and exert anti‐inflammatory and anti‐fibrotic effects that may enhance skin wound healing in horses. Abstract : Background – Wounds in horses often exhibit sustained inflammation and inefficient vascularization, leading to excessive fibrosis and clinical complications like "proud flesh". Orf virus‐derived proteins, vascular endothelial growth factor (VEGF)‐E and interleukin (ovIL)‐10, enhance angiogenesis and control inflammation and fibrosis in skin wounds of laboratory animals. Hypothesis/Objectives – The study aimed to determine if equine dermal cells respond to VEGF‐E and ovIL‐10. Equine dermal cells are expected to express VEGF and IL‐10 receptors, so viral protein treatment is likely to alter cellular gene expression and behaviour in a manner conducive to healing. Conclusions and clinical importance – This study shows that VEGF‐E and ovIL‐10 are active on equine dermal cells and exert anti‐inflammatory and anti‐fibrotic effects that may enhance skin wound healing in horses. Résumé: Contexte: Les plaies chez le cheval présentent souvent une inflammation prolongée et une vascularisation inefficace menant à une fibrose excessive et des complications appelées «proud flesh». Les protéines dérivées du virus Orf, le VEGF‐E (vascular endothelial growth factor) et l'interkeukine (ovIL)‐10, améliorent l'angiogenèse et contrôle l'inflammation et la fibrose des plaies cutanées des animaux de laboratoire. Hypothèses/Objectifs: L'étude a pour but de déterminer si les cellules dermiques équines répondent à VEGF‐E et ovIL‐10. Il est attendu que les cellules dermiques équines expriment les récepteurs à VEGF et IL‐10, le traitement aux protéines virales pourrait ainsi modifier l'expression génétique cellulaire et le comportement menant ainsi à la cicatrisation. Sujets: Les échantillons cutanés étaient prélevés de la paroi thoracique latérale de deux chevaux sains de race pur‐sang. Méthodes: Les cellules dermiques équines ont été isolées à l'aide d'une méthode d'extraction cutanée et leur phénotype a été évalué par immunofluorescence. Les cellules ont été traitées avec des protéines recombinantes avec ou sans stimuli inflammatoires. L'expression génique a été examinée par PCR standard et quantitative par transcription inverse. Le comportement cellulaire a été évalué par test d'abrasion. Résultats: Les cellules cultivées étaient à moitié des fibroblastes vimentin +ve et à moitié des cellules musculaires lisses alpha actin +ve et des myofibroblastes vimentin +ve . Le VEGF‐E ont augmenté l'expression d'ARNm Il‐10 tandis que l'expression d'ARNm de collagenase‐1 et VGEF‐1 était augmenté par ovIL‐10. Pour les cellules exposées à un stimulus inflammatoire, les deux traitements ont ralenti l'expression d'ARNm de TNF et exacerbé l'expression de protéines chimio attractive de monocyte. Les protéines virales n'ont pas non plus influencées la migration cellulaire. Conclusions et importance clinique: Cette étude montre que VEGF‐E et ovIL‐10 sont actifs sur les cellules dermiques équines et présentent des effets anti‐inflammatoires et anti‐fibrotiques qui pourraient améliorer la cicatrisation des plaies cutanées du cheval. Resumen: Introducción: Las heridas en los caballos a menudo exhiben inflamación continuada y vascularización ineficaz, lo que lleva a una fibrosis excesiva y complicaciones clínicas tales como "carnosidad". Proteínas derivados de virus Orf, factor de crecimiento endotelial vascular –E (VEGF) y la interleuquina (ovIL ‐10), mejoran la angiogénesis y el control de la inflamación y fibrosis en heridas de la piel de animales de laboratorio. Hipótesis/Objetivos: El objetivo del estudio fue determinar si las células dérmicas equinas responden a VEGF‐E y ovIL‐10. Se espera que las células dérmicas equinas expresen receptores de VEGF e IL‐10, así que el tratamiento con proteína viral podría alterar la expresión de genes celulares y su comportamiento de modo que favorecieran la cicatrización. Animales: muestras de piel se recogieron de la pared torácica lateral de dos caballos de pura sangre sanos. Métodos: células dérmicas equinas se aislaron utilizando un método de explante de piel y su fenotipo fue evaluado por inmunofluorescencia. Las células se trataron con proteínas recombinantes, con o sin estímulo inflamatorio. La expresión génica se examinó mediante PCR de transcriptasa inversa estándar y cuantitativa. El comportamiento de la célula se evaluó en pruebas de rasguño. Resultados: Las células cultivadas fueron mitad fibroblastos vimentina + y la otra miofibroblastos actina alfa de musculo liso + y vimentina +. VEGF‐E aumento de la expresión basal de IL‐10 mRNA, mientras que ;a expresión de mRNA de VEGF‐A y colagenasa‐1 se incrementó al tratar con ovIL‐10. En las células expuestas al estímulo inflamatorio, ambos tratamientos inhibieron la expresión de mRNA del factor de necrosis tumoral, y ovIL‐10 incrementó la expresión de la proteína quimiotáctica de monocitos. Ninguna proteína viral afectó en gran medida la migración celular. Conclusiones e importancia clínica: Este estudio demuestra que el VEGF‐E y la ovIL‐10 son activos en las células dérmicas equinas y ejercen efectos anti‐inflamatorios y anti‐fibróticos que pueden mejorar la cicatrización de heridas en la piel de caballos. Zusammenfassung: Hintergrund: Wunden bei Pferden zeigen oft eine ausgedehnte Entzündung und ungenügende Durchblutung, was zu exzessiver Fibrose und klinischen Komplikationen wie „wildes Fleisch" führt. Aus Orf Virus gewonnene Proteine, Vascular Endothelial Growth Faktor (VEGF)‐E und Interleukin (ovIL)‐10, steigern die Angiogenese und kontrollieren die Entzündung und Fibrose bei Hautwunden von Labortieren. Hypothese/Ziele: Diese Studie zielte darauf ab zu bestimmen, ob Hautzellen von Pferden auf VEGF‐E und ovIL‐10 reagieren. Es wird erwartet, dass equine Dermalzellen VEGF und IL‐10 Rezeptoren exprimieren, daher ist es wahrscheinlich, dass eine virale Proteinbehandlung die zelluläre Genexprimierung und das Genverhalten in einer Art und Weise ändert, die der Heilung zuträglich ist. Tiere: Es wurden Hautproben von der lateralen Thoraxwand von zwei gesunden Vollblutpferden genommen. Methoden: Es wurden Dermalzellen von Pferden mittels Hautexplantiermethode isoliert und ihr Phänotyp mittels Immunfluoreszenz ermittelt. Die Zellen wurden mit rekombinanten Proteinen behandelt, mit oder ohne Entzündungsstimuli. Die Genexprimierung wurde mittels Standard und quantitativer Reverser Transkriptase PCR untersucht. Das Zellverhalten wurde mittels Scratch Assay evaluiert. Ergebnisse: Die kultivierten Zellen bestanden zur Hälfte aus Vimentin +ve Fibroblasten und zur Hälfte aus alpha glatter Muskulatur Actin +ve und Vimentin +ve Myofibroblasten. VEGF‐E erhöhte die basale Exprimierung von IL‐10 mRNA, während VEGF‐A und Kollagenase‐1 mRNA Exprimierung durch ovIL‐10 zunahm. In jenen Zellen, die den Entzündungsstimulatoren ausgesetzt waren, dämpften beide Behandlungen die Exprimierung der mRNA des Tumor Nekrose Faktors, und ovIL‐10 erhöhte die Exprimierung von Monozyten Chemoattractant Protein. Keines der Virenproteine beeinflusste die Zellmigration drastisch. Schlussfolgerungen und klinische Bedeutung: Diese Studie zeigt, dass VEGF‐E und ovIL‐10 aktiv wirken auf Hautzellen der Pferde und eine entzündungshemmende sowie eine anti‐fibrosierende Wirkung ausüben, die die Wundheilung bei Pferden verbessert. 要約: 背景: 馬の創傷は持続的な炎症と血管新生不全を起こし、過剰な線維化と臨床的に「過剰肉芽(pround flesh)」と呼ばれる合併症を引き起こす。オルフウィルス由来蛋白である内皮血管増殖因子E(VEGF‐E)およびインターロイキン−10(ovIL‐10)は、皮膚創傷の実験動物モデルにおいて、血管新生を促進し、炎症と線維化を抑制することが示されている。 仮説/目的: 本研究の目的は、馬の真皮細胞のVEGF‐EおよびovIL‐10に対する反応性を調査することである。馬の真皮細胞はVEGFおよびIL‐10の受容体を発現しているため、ウィルス蛋白治療が、創傷治癒を助長する細胞遺伝子発現変化および細胞動態変化を起こす可能性がある。 供与動物: 2頭の健康なサラブレッド馬の胸部側面壁より得た皮膚サンプルを培養した。 方法: 馬の真皮細胞は皮膚移植片培養法によって分離し、免疫蛍光抗体法によって表現型を調べた。細胞は組み換え蛋白の存在下かつ炎症刺激有りもしくは無しで処理した。遺伝子発現は標準的な定量逆転写PCRによって測定した。細胞動態の評価には、スクラッチアッセイを用いた。 結果: 培養細胞は半数がビメンチン陽性線維芽細胞で、半数がα平滑筋アクチン陽性かつビメンチン陽性筋線維芽細胞であった。VEGF‐EはIL−10のmRNAの基礎発現量を増加させ、一方で、VEGF‐Aとコラゲナーゼ−1のmRNA発現量はovIL‐10によって増加した。炎症刺激を受けた細胞では、いずれのウィルス蛋白処理も腫瘍壊死因子mRNAの発現を減少させ、ovIL‐10は単球走化性因子の発現を増加させた。いずれのウィルス蛋白も細胞移動には大きく関与しなかった。 摘要: 背景: 马的伤口经常出现持久性炎症, 以及无法血管化, 造成过度的纤维化, 出现"赘肉"这种临床并发症。内皮细胞血管化生长因子(VEGF)‐E和白介素(ovIL)‐10, 是羊痘疮病毒衍生蛋白, 可增强了血管再生, 并且控制实验动物皮肤伤口的炎症和纤维化。 假设/目的: 研究目的是确定是否VEGF‐E和ovIL‐10对马真皮细胞有效。预计马真皮细胞表达VEGF‐E和ovIL‐10受体, 这样病毒蛋白治疗可能改变细胞基因表达和运转方式, 使其有利于伤口愈合。 动物: 样本收集自两匹健康纯血马的胸壁两侧皮肤。 方法: 使用皮肤移植方法分离马真皮细胞, 用免疫荧光评估其表型。细胞用重组蛋白处理, 有或没有炎性刺激。使用标准和定量反转录PCR检查基因表达。划痕试验评估细胞转运。 结果: 培养的细胞是半波形蛋白 +ve 成纤维细胞和半α平滑肌肌动蛋白 +ve, 以及波形蛋白肌成纤维细胞 +ve 。VEGF‐E 提高了IL‐10 mRNA的基础表达, 而ovIL‐10提高了VEGF‐A和胶原蛋白酶‐1mRNA的表达。对于暴露于炎性刺激的细胞, 两种处理抑制肿瘤坏死因子mRNA表达, 以及ovIL‐10加剧单核细胞趋化蛋白表达。病毒蛋白都不会很大程度影响细胞迁移。 结论和临床意义: 本研究发现VEGF‐E和ovIL‐10在马真皮细胞上具有活性, 其施加的抗炎和抗纤维化作用可以增强马的伤口愈合。 Resumo: Contexto: Feridas em equinos frequentemente apresentam inflamação crônica e vascularização ineficiente, ocasionado fibrose excessiva e tecido de granulação. Proteínas derivadas de Orf‐vírus, fator de crescimento endotelial vascular (VEGF)‐E e interleucina‐10 (ovIL‐10), aumentam a angiogenese, controlam a inflamação e a fibrose em feridas de animais de laboratório. Hipótese/Objetivos: O estudo teve como objetivo determinar se as células dérmicas de equinos respondem a VEGF‐3 e ovil‐10. É esperado que células dérmicas de equinos expressem receptores para VEGF e IL‐10, desta forma, é provável que o tratamento com as proteínas virais altere a expressão gênica e o funcionamento celular, tendendo à cicatrização. Animais: As amostas de pele foram coletadas da lateral do tórax de dois equinos da raça Puro Sangue Inglês. Resultados: As células cultivadas foram metade fibroblastos vimentina +ve e a outra metade músculo liso alpha actina +ve e miofibroblastos vimentina ve+ . VEGF‐E aumentou a expressão basal de mRNA de IL‐10, enquanto a expressão VEGF‐A e de colagenase‐1 foi aumentada por ovIL‐10. Em células expostas a estímulo inflamatório, ambos os tratamentos reduziram a expressão de mRNA de fator de necrose tumoral, e ovIL‐10 exacerbou a expressão de proteína quimiotática de monócitos. Tampouco a proteína viral influenciou a migração celular com grandeza. Conclusões e importância clínica: Este estudo demonstrou que VEGF‐E e ovIL‐10 são ativas em células dérmicas de equinos e exerce efeitos antiinflamatórios e antifibróticos que provavelmente melhorem a cicatrização em equinos.